„Kwestia ukraińska” w myśli politycznej Mariana Ursyna Zdziechowskiego 1918–1939 - Marszał, Maciej (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The issue of creation of good neighborly political relations with the nations belonging to the newly born in 1918 independent Republic of Poland were among the pressing problems of early Polish eastern policy. In the group of Polish intellectuals there were university professors, who often stressed the need good neighborly relations in this part of Europe. One of the propagators of the Central and Eastern European agreement was professor and rector of the Stefan Batory University in Vilnius Marian Ursyn Zdziechowski 1861–1938. The political thought of Marian Zdziechowski on the Ukrainian issue was characterized as harmony with the eastern national minority. It remained in line with the general political formula of Polish conservatives and their political postulates concerning the eastern policy of Poland. It is worth noting that Zdziechowski the unlike his conservative colleagues, such as Bocheński brothers, Jan Stanisław Łoś and many others, had an unusually realistic view on the issue of treatment of the Ukrainian minority. He was far from fanatical optimism of Polish-Ukrainian reconciliation, but even further from the nationalistic politics enlarged by the National Democracy, which assumed mass polonization of the Ukrainians. Zdziechowski’s program can be included in the concept of assimilation of the Ukrainians with simultaneous respect for their rights. His views were more akin to the postulates of Polish socialists, such as Leon Wasilewski and Tadeusz Hołówko, than to his native conservative views.
Keywords: Ukraińcy; Polska; myśl polityczna; sąsiedztwo